ANALISIS PENGUKURAN KINERJA RUMAH SAKIT DENGAN PENERAPAN METODE BALANCED SCORECARD (Studi Kasus Pada RSUD “Kanjuruhan” Kepanjen Kabupaten Malang) - Laila Yulita Anisak; Didied Poernawan Affandy (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
The purpose of this research is to measure performance RSUD “Kanjuruhan” Kepanjen Kabupaten Malang by using the concept Balanced Scorecards referring to four perspective which are, customers perspective, financial perspective, internal business process perspective, and also growth and learning perspective. The research used descriptive method by using secondary data among years of 2010 – 2012 and primary data to measure employees and patients satisfaction The results showed that the performance of RSUD